From teacher to tutor: examining why school teachers leave the service to be private tutors - Soon, Jocelyn Si Lin (2017)
The words “private tuition” are no doubt a part of the average Singaporean student’s vocabulary, since it has become a mainstream activity for many of them. However, more former school teachers are beginning to take up private tuition as well – as tutors. With numerous news reports highlighting the trend of school teachers leaving the teaching service to become private tutors, it would suggest that many capable and valuable teachers are taking their skills to the private tuition industry. Why then, do these former school teachers elect to enter a profession where the central task – teaching – essentially remains the same? To understand this trend, this study seeks to identify the relation between the (1) push factors that compel school teachers to leave the teaching service, and the (2) pull factors that present the appeal of being a private tutor. In doing so, this study also hopes to shed light on areas for improvement within the teaching service so that adequate support can be provided to current and future teachers.